Trends in Research on Problem-Based Learning (PBL) Model in Enhancing Scientific Literacy - Inayatil Baqy; Agus Abhi Purwoko; Lalu Rudyat Telly Savalas; Aris Doyan (Balai Publikasi Indonesia, 2025)
Problem-Based Learning (PBL) is an effective instructional model for encouraging students to think critically, solve contextual problems, and develop scientific literacy through investigation and analysis activities. This study aims to examine the trends and development of research related to the application of the PBL model in enhancing students' scientific literacy through a bibliometric approach over the period 2016–2025. A descriptive bibliometric analysis was conducted on 1,000 documents retrieved from Google Scholar using Publish or Perish and Dimensions.ai software. The data were analyzed using VOSviewer to map keyword co-occurrence, visualize topic trends (overlay visualization), and assess research density (density visualization). The results reveal a significant increase in publications after 2019, with prominent clusters focusing on STEM integration, critical thinking skills, learning effectiveness, and the role of teachers in promoting scientific literacy. The overlay visualization further highlights a growing emphasis on creative thinking skills, contextual approaches, and scientific literacy in recent research. This study recommends further exploration of underrepresented aspects, such as digital literacy, scientific attitudes, and interdisciplinary approaches grounded in local wisdom